2016
DOI: 10.4110/in.2016.16.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Roles of MAPK Phosphatases in Cancer

Abstract: The mitogen-activated protein kinases (MAPKs) are key regulators of cell growth and survival in physiological and pathological processes. Aberrant MAPK signaling plays a critical role in the development and progression of human cancer, as well as in determining responses to cancer treatment. The MAPK phosphatases (MKPs), also known as dual-specificity phosphatases (DUSPs), are a family of proteins that function as major negative regulators of MAPK activities in mammalian cells. Studies using mice deficient in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 126 publications
(152 reference statements)
5
138
0
1
Order By: Relevance
“…DUSP1 was the first identified family member, which is implicated in diverse biological events such as inflammation, cancer, metabolism, and diabetes [53]. DUSP1 is expressed in a variety of tissues with the highest levels being observed in the lung [37], and it is induced in the heart upon disease stimulation [54].…”
Section: Dusps In Cardiac Remodeling Through Mapk Regulationmentioning
confidence: 99%
“…DUSP1 was the first identified family member, which is implicated in diverse biological events such as inflammation, cancer, metabolism, and diabetes [53]. DUSP1 is expressed in a variety of tissues with the highest levels being observed in the lung [37], and it is induced in the heart upon disease stimulation [54].…”
Section: Dusps In Cardiac Remodeling Through Mapk Regulationmentioning
confidence: 99%
“…Phosphatase overexpression is oncogenic in different tumor types, but the signaling mechanisms remain unclear (Julien et al, 2007(Julien et al, , 2011. Recent work indicates that overexpressed phosphatases increase the malignancy of cancers that have a hyper-activated MAPK/ERK pathway (Julien et al, 2007;Low and Zhang, 2016;De Vriendt et al, 2013). Our result in the previous section suggested a mechanism through which overexpression of ERKspecific phosphatases sustains MEK phosphorylation levels ( Figures 4F and 4H).…”
Section: Pairwise Overexpression Analysis Reveals Phosphatase Sustainmentioning
confidence: 52%
“…Phosphatase overexpression is observed to drive tumor progression with unclear signaling mechanisms (Julien et al, 2011;Low and Zhang, 2016;De Vriendt et al, 2013). We indicated that rather than directly activating a cancer-driven signaling pathway, overexpression of ERKspecific phosphatases modulates signaling dynamics that leads to prolonged proliferative signal in cells.…”
Section: Discussionmentioning
confidence: 99%
“…22 Recently, more and more studies show that MAPK has a critical influence on tumor chemoresistance. 23 PI3K-Akt plays a critical role in the chemoresistance of cancer cells as an important regulatory pathway for cell proliferation. 24 The abnormal activation of PI3K-Akt can lead to a massive proliferation of cancer cells and reduce the efficacy of chemotherapy drugs.…”
Section: Identification Of Chemotherapy Response Related Functionsmentioning
confidence: 99%